Hip-Hop Culture as a Device for Non-Formal, Emancipatory, and Liberating Education (Interdisciplinary Studies Journal, 2024)
Hip-Hop, as a hybrid cultural movement, transcends borders and challenges social, political, and cultural structures. Its artistic expressions, such as graffiti, breakdancing, MCing, and DJing, form a productive discourse that reflects on themes such as urbanity, black identity, and resistance. Therefore, the objective was to investigate, through a bibliographic study, the potential of the Hip-Hop cultural movement as a tool for emancipatory and liberating education, conducted in a non-formal way. The main findings show that through Hip-Hop, educators can explore themes relevant to the reality of students in an interdisciplinary manner, contextualized with the students' lived experiences, promoting a more inclusive and emancipatory education. However, few studies have adopted Hip-Hop as a didactic tool. By recognizing the pedagogical potential of Hip-Hop, especially in diverse school contexts, space is created for critical reflection on power, identity, and social transformation, contributing to the construction of a more just and democratic society.
Keywords: Counterculture; Popular Education; Art; Transformation